2007
DOI: 10.1111/j.1365-2966.2006.11267.x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray emission from planetary nebulae calculated by 1D spherical numerical simulations

Abstract: We calculate the X‐ray emission from both constant and time‐evolving shocked fast winds blown by the central stars of planetary nebulae (PNe) and compare our calculations with observations. Using spherically symmetric numerical simulations with radiative cooling, we calculate the flow structure and the X‐ray temperature and luminosity of the hot bubble formed by the shocked fast wind. We find that a constant fast wind gives results that are very close to those obtained from the self‐similar solution. We show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…This is consistent with the previous theoretical work of Akashi et al (2007), who showed that diffuse X-ray emission can come from a shocked stellar wind whose velocity is rapidly increasing in the first 1000 yrs of post-AGB evolution.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This is consistent with the previous theoretical work of Akashi et al (2007), who showed that diffuse X-ray emission can come from a shocked stellar wind whose velocity is rapidly increasing in the first 1000 yrs of post-AGB evolution.…”
Section: Discussionsupporting
confidence: 81%
“…In the post-AGB stage the stellar parameters are determined by the mass of the central hot object that remains after the hydrogen envelope has been expelled. Previous 1D numerical work by Akashi et al (2007) and Steffen et al (2008) has shown that it is important to take into account the time history of the stellar wind as it increases in velocity and decreases in mass-loss rate over the few hundred years after the AGB envelope is ejected. In order to explain the low X-ray temperatures, either the X-rays come from wind shocked while the velocity was still low (vw < 500 km s −1 ), or some physical process operates to produce large quantities of gas at about a million degrees even when the stellar wind velocity is higher than 1000 km s −1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other possibilities include a rapid weakening of the fast wind in terms of mass loss, a slower moderate velocity wind of ≃ 500 km/s (post-AGB wind), or two opposite jets (collimated fast wind) as discussed in Akashi et al (2007).…”
Section: Planetary Nebulaementioning
confidence: 99%
“…However, the understanding of their origin, structures and evolution is just beginning with a better coverage of the entire electromagnetic spectrum (Kwok 2005). In particular, the nature and origin of their extended, spatially resolved X-ray emission is under close investigation since the launch of Chandra and XMM-Newton X-ray observatories (Akashi et al 2007 and references therein). PNe are formed by the interaction of a tenuous fast wind with a copious slow Asymptotic Giant Branch (AGB) wind, that produces either elliptical or bipolar PNe (Stute & Sahai ⋆ Corresponding author: e-mail: adecourchelle@cea.fr Frank & Mellema 1994).…”
Section: Planetary Nebulaementioning
confidence: 99%